2020
DOI: 10.1002/ffj.3626
|View full text |Cite
|
Sign up to set email alerts
|

Techniques for essential oil extraction from kaffir lime and its application in health care products—A review

Abstract: Kaffir lime (Citrus hystrix DC) is a tropical plant with aromatic leaves. It produces fruits that are used in Asian cuisines as a flavoring agent. Essential oil from the leaves and peel of kaffir lime is a complex mixture of volatile and semi‐volatile compounds. It is rich in bioactive molecules that act synergistically to improve the well‐being of an individual. The method of extraction is important as it affects the quality and quantity of essential oil significantly. Kaffir lime oil is used as raw material … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…It allows obtaining a relatively high yield of obtained oil with the use of an eco-friendly solvent. Though raw materials are directly immersed in boiling water, the water acts as a protective barrier and prevents the extracted essential oil from overheating to a certain extent [ 11 ]. In earlier studies that used the hydrodistillation technique to obtain essential oils from fresh kaffir lime peel, the yield was 0.16–2.10% [ 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It allows obtaining a relatively high yield of obtained oil with the use of an eco-friendly solvent. Though raw materials are directly immersed in boiling water, the water acts as a protective barrier and prevents the extracted essential oil from overheating to a certain extent [ 11 ]. In earlier studies that used the hydrodistillation technique to obtain essential oils from fresh kaffir lime peel, the yield was 0.16–2.10% [ 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is confirmed in the literature, where the potential therapeutic effects of Citrus hystrix DC on metabolic disorders have been demonstrated [ 10 ]. Kaffir lime essential oils are utilized in the production of cosmetics [ 11 ]. According to recent literature reports, kaffir lime essential oil peel is safe for the skin in an in vitro model [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…This carbon–carbon double bond is highly reactive when exposed to oxidizing gases. Reacting with oxidizing gases, monoterpene is converted to its derivative compounds (Suresh et al, 2021). This study revealed that MVD could retain VOCs when the vacuum technique was used to dry the C. hystrix leaves without oxygen.…”
Section: Resultsmentioning
confidence: 99%
“…There have been various methods developed for EO extraction, mainly including hydrodistillation, steam distillation, solvent extraction, and supercritical fluid extraction. , The composition and content of chemical compounds in the extracted EOs are varied according to the different extraction methods. As to the therapeutic EOs, their effect on the disease treatment may be potentially affected by the extraction methods.…”
Section: Resultsmentioning
confidence: 99%